Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
Proceedings 2015 Network and Distributed System Security Symposium 2015
DOI: 10.14722/ndss.2015.23162
|View full text |Cite
|
Sign up to set email alerts
|

Upgrading HTTPS in mid-air: An Empirical Study of Strict Transport Security and Key Pinning

Abstract: Abstract-We have conducted the first in-depth empirical study of two important new web security features: strict transport security (HSTS) and public-key pinning. Both have been added to the web platform to harden HTTPS, the prevailing standard for secure web browsing. While HSTS is further along, both features still have very limited deployment at a few large websites and a long tail of small, security-conscious sites. We find evidence that many developers do not completely understand these features, with a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
56
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(57 citation statements)
references
References 47 publications
0
56
0
1
Order By: Relevance
“…Just to mention a few relevant works, previous evaluations focused on other aspects of web security, like remote JavaScript inclusion [19], DOM-based XSS [15], mixed content websites [7], authentication cookies [6] and HSTS [14].…”
Section: Large-scale Analysis Of the Webmentioning
confidence: 99%
“…Just to mention a few relevant works, previous evaluations focused on other aspects of web security, like remote JavaScript inclusion [19], DOM-based XSS [15], mixed content websites [7], authentication cookies [6] and HSTS [14].…”
Section: Large-scale Analysis Of the Webmentioning
confidence: 99%
“…Kranch and Bonneau [34] studied how HSTS and key pinning are deployed in practice, and found that even such simple proposals to enhance the HTTPS security are challenging to implement. We note that key pinning is overridden by Chrome 47.0 when the server certificate is signed by an imported root certificate.…”
Section: Recommendations For Safer Tls Proxyingmentioning
confidence: 99%
“…Finally, Bates et al [11] introduce CERTSHIM, a tool for certificate verification retrofitting that is dynamically hooked to SSL and data transport libraries, while Kranch and Bonneau [25] reveal that cookies can be leaked from domains that implement key pinning to malicious scripts in HTTP domains they load resources from.…”
Section: Related Workmentioning
confidence: 99%